Creating Chaos Online Disinformation and Subverted Post-Publics - Zelenkauskaite, Asta (University of Michigan Press, 2022)
With the prevalence of disinformation geared to instill doubt rather than clarity, Creating Chaos Online unmasks disinformation when it attempts to pass as deliberation in the public sphere and distorts the democratic processes. Asta Zelenkauskaitė finds that repeated tropes justifying Russian trolling were found to circulate across not only all analyzed media platforms' comments but also across two analyzed sociopolitical contexts suggesting the orchestrated efforts behind messaging. Through a dystopian vision of publics that are expected to navigate in the sea of uncertain both authentic and orchestrated content, pushed by human and nonhuman actors, Creating Chaos Online offers a concept of post-publics. The idea of post-publics is reflected within the continuum of treatment of public, counter public, and anti-public. This book argues that affect-instilled arguments used in public deliberation in times of uncertainty, along with whataboutism constitute a playbook for chaos online.